The Children of Lincoln : White Paternalism and the Limits of Black Opportunity in Minnesota, 1860-1876 - Green, William D. (William Davis), 1950- (Book collections on Project MUSE., 2018)
"The Children of Lincoln takes an intimate look at African-American civil rights in Minnesota during the pivotal fifteen years following the Emancipation Proclamation and in the wake of the Civil War. Framed around the lives of four white patrons who worked for black freedom (Minnesota's "Children of Lincoln"), Green's history lays bare an era when many white patrons, seemingly content with the notion that African Americans were now legally "free," turned their sights to other causes, abandoning their earlier work towards equality. In truth, African Americans in Minnesota were entering a new era of darkness--while not in the same way as in the South, where white supremacy and racial violence spread with horrific force--but still an era where racism, hatred, and growing prejudice kept them from many of the rights that were seemingly now theirs"--